Northwest Passage Project 2019 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - Ship-Based Research Support, Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2021)
The Northwest Passage Project 2019 was a US National Science Foundation funded program in collaboration with the Swedish Polar Research Secretariat to explore the changing Arctic through an innovative expedition onboard the Swedish Icebreaker Oden. The science activities were motivated by the overarching goal to understand how waters of the Canadian Arctic Archipelago have changed as a consequence of the secular warming trend over the Arctic Circle.

Undergraduate and graduate students participated in the expedition along with scientists, historians, journalists, and a documentary film crew. The expedition engaged diverse audiences through real time interactions from sea, a high definition 2-hour documentary, and related community events. Visit https://northwestpassageproject.org for more information about the expedition and the research projects.

The data presented here are the meteorological, oceanographical and ship data collected onboard Icebreaker Oden during the expedition Northwest Passage Project 2019.

This data set contains meteorological, oceanographical and ship data collected onboard IB Oden during the expedition Northwest Passage Project 2019, which was a research cruise to the Canadian Arctic Archipelago.

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographical variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Heading, Water depth.

A "Parameter list" which describes the dataset is attached.

Quality Information: No quality check or other processing of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Northwest Passage Project 2019 var en amerikansk forskningsexpedition till Nordvästpassagen med isbrytaren Oden. Expeditionen finansierades av National Science Foundation och genomfördes i samarbete med Polarforskningssekretariatet. Det övergripande vetenskapliga syftet var att undersöka hur havsmiljön i Arktiska Kanada påverkas av ett varmare klimat. Mer information om expeditionen och den forskning som bedrevs ombord finns i den engelskspråkiga beskrivningen samt på https://northwestpassageproject.org
Data som presenteras här är meteorologiska och oceanografiska data, samt skeppsdata, insamlade under expeditionen Northwest Passage Project 2019.

Data innehåller meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden under forskningsexpeditionen Northwest Passage Project 2019.

Meteorologiska variabler: Lufttemperatur, luftfuktighet, vindriktning/-hastighet, lufttryck, molnhöjd/molnighet, fotosyntetiskt aktiv strålning (PAR).

Oceanografiska variabler: Havsvattentemperatur, konduktivitet, salthalt, ljudhastighet.

Skeppsdata: Position, fart, kurs, stävad kurs, vattendjup.

En ”Parameter list” finns bilagd som beskrivning av data.

Data har inte genomgått kvalitetsgranskning. Användare behöver ta hänsyn till det i all hantering och vidare analys.
Northwest Passage Project 2019 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden
Keywords: ATMOSPHERE; ATMOSPHERIC WINDS; WIND SPEED; WIND DIRECTION; VISIBILITY; WEATHER EVENTS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; PRECIPITATION AMOUNT; PRECIPITATION RATE; HUMIDITY; CLOUD FREQUENCY; CLOUD BASE HEIGHT; ATMOSPHERIC PRESSURE; SEA LEVEL PRESSURE; ATMOSPHERIC PRESSURE MEASUREMENTS; SALINITY/DENSITY; SALINITY; CONDUCTIVITY; PHOTOSYNTHETICALLY ACTIVE RADIATION; WATER TEMPERATURE; WATER DEPTH; Atmospheric conditions; Atmosfäriska förhållanden; Coordinate reference systems; Referenskoordinatsystem; Hydrography; Hydrografi; Meteorological geographical features; Geografiska meteorologiska förhållanden; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Location; Positionering